Analysis of the Restructuring of Bad Credit Agreements in Conventional Banks - Ria Juliana Siregar (Manunggal Halim Jaya, 2026)
Credit restructuring is a crucial mechanism in the banking sector designed to protect the interests of both creditors and debtors who are experiencing financial distress. In essence, restructuring serves as a remedial policy aimed at preventing loans from deteriorating into non-performing status while preserving the continuity of viable businesses. Rather than immediately enforcing collateral execution or initiating legal proceedings, banks may modify the original loan agreement to restore the borrower’s repayment capacity This process typically involves adjusting credit terms through interest rate reductions, extension of loan maturities, rescheduling of installment payments, conversion of short-term obligations into longer-term facilities, or, in certain cases, partial principal reduction. These measures are intended to realign debt obligations with the borrower’s current cash flow conditions. In Indonesia, regulatory frameworks established by the Financial Services Authority (OJK) and Bank Indonesia provide a strong legal and prudential basis to ensure that restructuring is conducted transparently, objectively, and in accordance with sound risk management principles. For creditors, restructuring minimizes potential losses, preserves asset quality, and prevents a sharp increase in non-performing loans that could weaken capital adequacy. For debtors, it offers financial relief, protects business sustainability, and helps maintain employment and economic productivity. Although risks such as moral hazard, repeated default, and legal disputes may arise, effective supervision, fair mediation, and continuous performance evaluation can mitigate these challenges. When implemented prudently, credit restructuring becomes a strategic instrument for safeguarding financial system stability, particularly during periods of economic uncertainty or crisis.